2010
DOI: 10.1093/jjco/hyq009
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Radiotherapy With or Without Chemotherapy for T3-4N0 Squamous Cell Carcinoma of the Maxillary Sinus and Nasal Cavity

Abstract: The treatment outcome was poor and local control was a major problem. High radiation dose, effective chemotherapy and elective neck irradiation for advanced nasal cavity cancers may improve disease control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 18 publications
2
40
1
Order By: Relevance
“…These reports appear to support our hypothesis. Further, Jang et al reported that the incidence of late neck recurrence was 3.3% in patients with T3-4 N0 maxillary sinus cancer, who underwent definitive radiotherapy without ENI [10]. As 66% of all participants received induction chemotherapy and 10% of them received concurrent chemotherapy in this report, it might be that systemic drug application has the capacity to eliminate occult micrometastases in regional lymphatics to a degree, comparable to that of ENI or surgery.…”
Section: Discussionmentioning
confidence: 57%
“…These reports appear to support our hypothesis. Further, Jang et al reported that the incidence of late neck recurrence was 3.3% in patients with T3-4 N0 maxillary sinus cancer, who underwent definitive radiotherapy without ENI [10]. As 66% of all participants received induction chemotherapy and 10% of them received concurrent chemotherapy in this report, it might be that systemic drug application has the capacity to eliminate occult micrometastases in regional lymphatics to a degree, comparable to that of ENI or surgery.…”
Section: Discussionmentioning
confidence: 57%
“…Yet, in spite of advancements in technology, there has been no significant improvement in the 5-year OS rate since the 1960s. However, retrospective studies have shown reduced radiation-induced toxicity with the use of IMRT in the adjuvant setting and LC rates equal to or better than 3D-CRT [7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In this study, we present the results of 11 patients with SNC treated with definitive RT or CRT, using a two-phase IMRT technique.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have shown surgery followed by postoperative RT has Electronic supplementary material The online version of this article (doi:10.1007/s13566-015-0226-3) contains supplementary material, which is available to authorized users. superior 5-year local control (LC) rates, ranging from 40 to 79 % [2,[5][6][7] compared with definitive RT or CRT ranging from 20 to 64 % [2,5,[8][9][10][11][12][13][14][15][16][17][18]. However, due to the proximity of SNCs to critical structures such as the brain, optic nerves, orbital contents, and carotid artery, surgery for very locally advanced SNC is often a difficult, if not unattainable, option [3].…”
Section: Introductionmentioning
confidence: 99%
“…Local control rates ranging from 14% to 53% have been reported. [24][25][26][27][28][29] However, many studies are marked by selection bias, and patients treated nonsurgically more often have locally advanced disease or are considered inoperable (Table 7). 23,28,[30][31][32][33] The use of induction chemotherapy for sinonasal squamous cell carcinomas has not been associated with improved local control or a survival advantage.…”
Section: Nonsurgical Management Of Sinonasal Malignanciesmentioning
confidence: 99%